Internalization Of Arabic Syntactic In The Interpretation Of Legal Verses - Aang Saeful Milah; Mohamad Rohman; Ahmad Najid Rasikhullah (Indonesian Journal of Arabic Studies, 2023)
Purpose: This study aims to explore the works of Islamic scholars both in the fields of fiqh, Arabic language and also books of interpretation to find out how the process of the scholars internalizing Arabic syntax in establishing shari'ah law. Design/ methods/approach: In this study, a descriptive qualitative approach is used to examine how Arabic syntax influences the interpretation of Quranic legal verses and the formulation of Sharia law. It includes an extensive literature review and textual analysis of primary texts like the Quran and Hadith, as well as secondary sources in the fields of fiqh and Arabic language. The research primarily relies on qualitative data, employing content analysis to identify themes and patterns in the internalization of Arabic syntax by Islamic scholars, enhancing our understanding of its impact on legal interpretations in Islamic jurisprudence. Findings: The study finds that subtle aspects of Arabic grammar, such as word order, verb tense, and sentence structure, significantly affect the derivation of legal rulings. These syntactic elements often lead to diverse interpretations, impacting the formulation of Islamic law across different schools of thought. Research implications: Â One of the key contributions of this research is the demonstration of how Arabic syntax serves as more than a linguistic tool; it is a critical component in the hermeneutics of Islamic law. This insight is pivotal for scholars, legal practitioners, and students of Islamic studies, offering a deeper appreciation of the complexity involved in interpreting sacred texts.